Comparison of 36 mg and 72 mg Ralgro® for suckling steer calves - Simms, D.D.; Bolze, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In order to evaluate whether a 72 mg Ralgro® dosage would improve growth response over 36 mg, 260 suckling steer calves on tow Kansas ranches were assigned to five implant treatments. In trial 1, 72 mg Ralgro® increased gain more than 36 mg Ralgro®. In trial 2, all implant treatments gave only a slight increase in growth rate over controls. Thus, the results are inconclusive and warrant more research before an accurate evaluation of 72 mg Ralgro® for suckling steer calves can be made.
Keywords: Beef; Steers; Implant; Growth rate